Malay and global literacy - Sew, Jyh Wee (Universiti Kebangsaan Malaysia, 2012)
Selected factors determining the success of Malay as a viable foreign language choice going forward are examined in this article. Attracting learners to select Malay as a foreign language within a vibrant formal learning environment in a globalist culture is vital to Malay maintenance. Arguably, a progressive language programme tailors the delivery and knowledge register of its language modules to maintain the motivation in learning the language. The discussion begins with a short introduction to Malay in Singapore by invoking the socio-historical context of Malay as a mother tongue taught in the national education system of Singapore. Three overlapping areas of language learning, namely learner profile, pedagogy and knowledge register are framed as the areas of concerned to maintain Malay language education at the tertiary and secondary school level, respectively. Following from the cross-examination, these variables are realigned in a learning framework towards a sustainable Malay language education.